Modulating Activity in the Prefrontal Cortex Changes Intertemporal Choice for Loss: A Transcranial Direct Current Stimulation Study - Xiong, Guanxing; Li, Xi; Dong, Zhiqiang; Cai, Shenggang; Huang, Jianye; Li, Qian (Frontiers in Human Neuroscience, 2019)
Intertemporal choice refers to decisions involving tradeoffs between costs and benefits occurring at different times. Studies have found that weighting the time and benefits during decision-making involves a complex neural network that includes the dorsolateral prefrontal cortex (DLPFC). However, in contrast to literature regarding intertemporal choice for gains, studies have not provided causal evidence that the DLPFC is involved in intertemporal choice for losses. We examined whether bifrontal transcranial direct current stimulation (tDCS) applied over the right and left prefrontal cortex can alter the balance of intertemporal preference in the loss condition. A total of 60 participants performed delay discounting tasks for losses while receiving either right anodal/left cathodal, left anodal/right cathodal, or sham stimulation. The results showed that participants tended to choose larger delayed losses after receiving left anodal/right cathodal tDCS. Left anodal/right cathodal tDCS significantly decreased the discounting rate compared with the sham stimulation. These findings confirm that DLPFC activity is critical during intertemporal decision-making for losses.